Solusi Modern untuk Mendaftarkan Peserta Didik Baru di Paud Melati berbasis Web - Nabilah Nur Zakiyyah; Nopika; Wasis Haryono (Universitas Serambi Mekkah, 2025)
The rapid development of information technology has prompted educational institutions, including Early Childhood Education (PAUD), to adopt a digital transformation. This study aims to design and develop a web-based information system for PAUD Melati as an innovative solution for managing information and New Student Registration (PPDB). The website is equipped with essential features such as a homepage showcasing a brief PAUD profile, available facilities, a collection of student achievements, educational trip documentation, and detailed profiles of the teaching staff. Additionally, the system includes a login and registration feature for users (parents or guardians) to access further services, including online student registration. The system follows the Software Development Life Cycle (SDLC) methodology, covering stages like needs analysis, design, implementation, testing, and maintenance. The results demonstrate that this system improves administrative efficiency and facilitates communication between PAUD and the community.